Undone - Slaughter, Karin 1971- (New York Delacorte Press, 2009)
As Georgia Bureau of Investigation agents Faith Mitchell and Will Trent try to connect two murders to a hit-and-run victim, Atlanta physician Sara Linton becomes more involved in the investigation--an investigation which soon culminates in the hunt for a sadistic serial killer
1
Keywords: Linton, Sara (Fictitious character) -- Fiction; Women physicians -- Fiction; Atlanta (Ga.) -- Fiction; Psychological fiction; Suspense fiction